Edukasi Pemanfaatan Quick Response Code Indonesian Standard (QRIS) di Negeri Leahari - Jusuf Leiwakabessy; Rahman Rahman; Harold J. D. Waas; Ronald D. Hukubun; Gresia Maiseka; Kelvin Sopahaluwakan (Jurnal Kabar Masyarakat, 2023)
Digital financial transactions in Indonesia continue to show an increasing trend from year to year, with a sharp increase in the last 3 years. Observing the accelerated implementation of the development of non-cash transactions and to improve the payment system, Bank Indonesia launched the Quick Response Code Indonesian Standard (QRIS) on 17 August 2019 which then as of 1 January 2020 requires all non-cash payments to use QRIS. QRIS is a QR Code standard created by Bank Indonesia to facilitate digital payments through server-based electronic money applications, electronic wallets, and mobile banking. Standardization is carried out so that transactions with QR Codes are made easier, faster, and safer because digital transactions can be monitored by regulators through one platform.